Analisis Pembagian Harta Warisan yang Masih Disewa oleh Pihak Ketiga (Studi Putusan Mahkamah Agung Nomor 1935 K/Pdt/2023) - Wanda Jaya Silaen; Hasim Purba; Sutiarnoto (CV. Creative Tugu Pena, 2024)
The aim of this research is to determine the ownership status of inherited assets that are still being rented by third parties, the distribution of inherited assets that are still being rented by third parties whose lease terms have not yet ended, and to analyze the judge's considerations in the Supreme Court Decision Number 1935 K/PDT/2023. The method used in this writing is a normative juridical research method, namely a method that refers to legal norms carried out by means of literature study. This research has a descriptive nature, and the data is analyzed qualitatively and conclusions are drawn deductively. The research results found that the ownership status of inherited assets that are still rented by third parties remains jointly owned by the heirs, without changing the ownership status of the inherited objects. Distribution of inherited assets in this condition can be done in several ways, such as selling the inherited object along with the rental rights, waiting for the lease period to end before dividing, or dividing the rental proceeds proportionally between the heirs. This is in line with the Supreme Court decision Number 1935 K/PDT/2023, where the judge emphasized the principle of justice in the distribution of inheritance by giving equal rights to all legal heirs, including ordering the disputed object to be vacated for sale and the proceeds of the sale to be divided equally among all heir. This decision strengthens the understanding that the heirs' rights to inherited assets are still recognized and protected, even though the objects of inheritance are being rented by a third party.